2003
DOI: 10.1186/ar732
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Heterogeneity and multifactoriality complicate diagnostics and our understanding of pathogenesis of rheumatoid arthritis (RA). The only accepted serologic parameter (rheumatoid factor [RF]) is not disease specific, nor are any of several novel RA autoantibodies. We aimed at identifying profiles instead of individual autoreactivities allowing for unambiguous prediction of RA. Selected RA autoantigens were tested by ELISA (RF and anti-cyclic citrullinated peptide [anti-CCP]) or Western blot (heavy-chain-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In our study, we enrolled consecutive ERA patients at disease onset without previous exposure to conventional or biological DMARDs in whom plasma levels of bone-derived biomarkers were assessed, finding that women older than 50 years old have higher DKK1 plasma levels than men older than 50 years old and higher RANKL plasma levels than men younger than 50 years old. Moreover, we found that in ERA patients, OPG plasma levels directly correlated with age at disease onset regardless of sex, as was previously demonstrated in healthy subjects (31) as well as in systemic diseases characterized by bone loss (32). This might reflect a compensatory self-defense mechanism against age-related osteoporosis.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, we enrolled consecutive ERA patients at disease onset without previous exposure to conventional or biological DMARDs in whom plasma levels of bone-derived biomarkers were assessed, finding that women older than 50 years old have higher DKK1 plasma levels than men older than 50 years old and higher RANKL plasma levels than men younger than 50 years old. Moreover, we found that in ERA patients, OPG plasma levels directly correlated with age at disease onset regardless of sex, as was previously demonstrated in healthy subjects (31) as well as in systemic diseases characterized by bone loss (32). This might reflect a compensatory self-defense mechanism against age-related osteoporosis.…”
Section: Discussionsupporting
confidence: 82%